PENGENALAN HIDROPONIK UNTUK MENINGKATKAN PENGETAHUAN PERTANIAN DI MI NU THORIQOTUS SA'DIYAH - Gusnia Rahma Risna; Riski Dwi Saputro (LPPM Institut Pendidikan Nusantara Global, 2025)
Interest in agriculture among young people is currently declining, especially among children still in elementary school. However, introducing agriculture from an early age is crucial to foster an understanding of environmental sustainability and food security. This community service program aims to introduce hydroponic farming methods to students at MI NU Thoriqotus Sa'diyah, Kudus, as a modern, accessible and practical agricultural pedagogy. The month-long program involved 37 students, using a method that involved participation and demonstration through an Agro-Schooling approach that focuses on hands-on practice. The steps involved socializing hydroponics using multimedia, forming study groups, sowing seeds, and mixing nutrient solutions. The results of this program showed an increase in students' knowledge and interest in hydroponic farming, accompanied by active participation at every stage.